Bacterial Symbionts of Soft Coral Lobophytum Sp. From Panjang Island, Jepara, Indonesia With Antimicrobial MDR TB Potency - Yuvianti Dwi Franyoto; Ahmad Fuad Masduqi; Sakti Muchlisin; Prasetyo Abi Widyananto; Sulistiyani Sulistiyani; Diah Permata Wijayanti; Lia Kusmita (Journal of Tropical Pharmacy and Chemistry, 2019)
Tubercolusis is a disease that attacks the lungs. The disease is caused by the bacterium mycobacterium tubercolusis. The bacteria mycobacterium tubercolusis can be killed by antibiotics. However, continuous use of antibiotics can cause bacterial resistance. So we need to find new drugs that can prevent multi-drug resistant tuberculosis. This study aims to determine the antibacterial activity of MDR TB from soft coral symbiont bacteria Lobophytum sp. There were 6 bacterial isolates obtained from soft coral Lobophytum sp. One isolate from Lobophytum-associated bacteria were successfully screened for antimycobacterial against MDR TB bacteria. PLO2 was found to inhibit the growth of MDR TB (MDR TB strain SIRE and R). Based on the results of identification with PCR, soft coral symbionts of PLO2 was closely related to Virgibacillus marismortui with homology of 99%.